Social capital of women who have been subjected to domestic violence - R. M. Sadykov; N. L. Bolshakova (Вестник университета, 2023)
The article studies social capital of women who have been subjected to domestic violence. Cruelty and domestic violence are not a new social phenomenon in modern society, being one of the most global and widespread problems around the world. Mistreatment of relatives and domestic violence do not depend on social and economic status, level of education and profession, ethnicity, and race. The manifestation of violence and abuse in family negatively affects health and well-being of women’s capital. The main features and characteristics of women who have been subjected to violence are altruism, self-sacrifice, unstable and low self-esteem, dependence on partner, social passivity, non-self-sufficiency, insecurity, fear of men and anxiety, isolation, etc. The situation of domestic violence has deteriorated dramatically during the COVID-19 pandemic. The number of family conflicts on domestic violence has increased all over the world. In 2020, the United Nations issued an appeal to the member countries to take enhanced measures to prevent domestic violence during quarantine. Family violence is an acute social problem on a global scale that needs to be addressed immediately. Russian society discusses a draft law aimed at preventing domestic violence. Its necessity is due to the increasing scale of domestic violence and family conflict.